Evaluating Critical Thinking in Computer Mediated Communication Discussions - Faizah Mohamad (UiTM Publisher, 2008)
This paper presents an investigation of whether computer mediated communication (CMC) can develop critical thinking in language classrooms. The research was conducted at a university branch campus in Malaysia over a period of 12 weeks. It involved three groups of learners in which each group was exposed to different discussion modes. The first group was exposed to a CMC discussion mode, the second group was exposed to a mixed mode of CMC and face-to-face (F2F) discussions and the third group had only the face-to-face mode of discussion. The critical thinking development in these three conditions was evaluated based on the content analysis method used by Newman, Johnson, Cochrane and Webb (1995). This research reports the findings which hopefully will give some insight to other teaching practitioners who are interested in incorporating IT in their classrooms